Characteristics of Modified Multiple-Choice Instrument to Measure High Order Thinking Skills for Ecosystem Subject - Armita Hildan Haniyah; Muslimin Ibrahim (Berkala Ilmiah Pendidikan Biologi (BioEdu), 2020)
The demand in the 21st century emphasizes that student shall possess high-order thinking skills. One of the alternative assessments that can be used to practice higher-order thinking skills is modified multiple-choice. Modified multiple-choice consists of two levels; the first level resembles traditional multiple-choice, while the second level is students’ reasons in answering the first level, aiming to encourage higher-order thinking skills. The study aims to describe the characteristics of modified multiple-choice for ecosystem subject. The development of the assessment instrument referred to the ADDIE model, which consisted of five stages, including analysis, design, development, implementation, and evaluation. The developed items are then validated by education and material experts to check the validity of items. The items of a multiple-choice assessment instrument are tested to 32 students of 10th graders at SMAN 19 Surabaya. Data analysis technique employed was descriptive analysis technique, including the analysis of validity and test results to determine the reliability value and level of difficulty. The results suggest that the modified multiple-choice assessment instrument was declared valid with a mode of 4, which was included in the “highly valid” category. The reliability value using Cronbach’s Alpha formula reached 0.63. Meanwhile, the difficulty index was evenly distributed, with percentages of 20% (easy), 53% (medium), and 27% (difficult). The modified multiple-choice questions for ecosystem subject are declared valid and reliable to measure the students’ abilities. Keywords: item characteristics, modified multiple-choice, validity, reliability, level of difficulty